Minimal Surfaces in Standard Three-Dimensional Geometry Sol3 - Masaltsev, L. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
We study minimal and totally geodesic surfaces in the standart three-dimensional geometry $Sol^3$ with the left-invariant metric $ds^2=e^{2z}dx^2+e^{-2z}dy^2+dz^2$. Mathematics Subject Classification: 53A10, 53C42.